PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BEI PERIDOE 2017-2020 - Carlos Calvin Boi Paruntungan Nababan; Remista Simbolon (Jurnal Ekonomis, 2021)
This research was made to test and understanding the effects of good corporate governance and profitability in earning management. Indicator used is the profit distribution approach. The population and sample for this research is companies in the chemical subsector who are registered in the Indonesia Stock Exchange for 2017 – 2020 (www.idx.co.id). Methods used are: Descriptive quantitative analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient determination, t test, double regression and F test. Results showed that the independent board of commissioners has no significant effect on earning management, management ownership has no significant effect on earning management, number of committee members has no significant effect on earning management, number of meetings has no significant effect on profit management, and profitability effects profit management. In conclusion, independent variables of this research have no effect on dependent variables.